IS ANCESTOR VENERATION COMPATIBLE WITH THE BIBLICAL FAITH? - Nürnberger, Klaus (Scriptura, 2008)
As part of a research project on ancestor veneration in the church this essay explores the stance of biblical witness on a few fundamental issues: (a) How important is past history for the biblical faith? (b) What is the role of the prime ancestors of Israel in the biblical faith? (c) Can the deceased mediate between humans and God? (d) Should the deceased exercise authority over the living? (e) Does respect, gratitude and love for one’s forebears imply dependency on them as superiors? (f) Does the exclusiveness of the biblical faith imply intolerance and religious imperialism? (g) Can African insights and metaphors be used to express the message of the gospel?